Aproveitamento de subprodutos dos frutos de Eugenia Dysenterica DC. : potencial para a produção de bioprodutos - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The present work had as objectives to carry out the phytochemical study of fruit by-products of Eugenia dysenterica DC. (Myrtaceae), develop and obtain standardized liquid and lyophilized extract, and evaluate antioxidant, antimicrobial, antibiofilm activities of the liquid extracts (ELQ) and lyophilized (ELF). Chapter 1 presents a bibliographical review on Eugenia dysenterica, where the main potential of the species for biological, food and industrial drugs are addressed, as well as its phytosociological and environmental aspects. Chapter 2 makes the pharmacognostic study for the establishment of quality control parameters of plant raw materials (by-products of husks and seeds), as well as identifies the components of essential oils of leaves, fruits and by-products of the fruits of Eugenia dysenterica. The qualitative phytochemical analysis revealed the presence of substances such as tannins and phenolic compounds. In addition, gallic acid and ellagic acid, identified by chromatography, corroborate previous studies that highlight their antioxidant and anti-inflammatory activities. The centesimal composition of the material, including the ash contents and intumescence index, is in accordance with the requirements established by the Brazilian Pharmacopoeia. -selinene, α- selinene, myrcene and β-pinene are the major compounds of essential oil from fruits, leaves and fruit by-products of Eugenia dysenterica. Chapter 3 presents the results of the optimization of the ultrasound-assisted extraction of total phenolic compounds from by-products of the fruits of Eugenia dysenterica. The optimization was performed with the aid of a Box-Benhken model and response surface methodology. Two optimal conditions were defined: 1 - proportion of plant material:solvent 0.01g/mL, 40 min time and ethanolic graduation of 30%; 2 - 0.19g/mL, 39 min and 46%. Chapter 4 presents the evaluation of antioxidant, antimicrobial, antibiofilm and toxicity activity in Artemia salina from liquid (ELQ) and lyophilized (ELF) extracts of Eugenia dysenterica. The broth microdilution test was used, which allowed to determine the Minimum Inhibitory Concentration (MIC) against strains of Gram(+), Gram(-) bacteria from bovine mastitis isolates and commercial isolates of chicken heart and liver. The results of antioxidant activity, determined by ABTS, FRAP and DPPH tests were respectively: ELQ: 1.633,13 μM trolox/g, 1.633,60 μM FeSO4/g and 73,35 g sample/g DPPH; ELF: 1.379,75 μM trolox/g, 1.692,09 μM FeSO4/g and 83,35 g sample/g DPPH. For antimicrobial activity, both presented MIC < 62.5 mg/mL, and MIC and MBC of 2.5 mg/mL for P. aeruginosa. ELQ showed antibiofilm action for S. coagulase (50 mg/mL) and Streptococcus spp. (12.5 mg/mL); ELF for P. aeruginosa (50 mg/mL; 12.5 mg/mL), E. coli (25 mg/mL). The ELQ presented a CL50 value of 863.440 μg/mL and the ELF of 1200.413 μg/mL versus toxicity in Artemia salina. These findings indicate that by-products of Eugenia dysenterica may be a promising source for sustainable bioinputs.
Keywords: Eugenia Dysenterica; Cagaita; Bioinsumos; Bioprodutos; Extração assistida por ultrassom (EAU); Eugenia Dysenterica; Cagaita; Bioinputs; Bioproducts; Ultrasound-assisted extraction; CIENCIAS BIOLOGICAS; CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS; FARMACIA::FARMACOGNOSIA